“MISSING IN ACTION”: THE SIGNIFICANCE OF BODIES IN AFRICAN BEREAVEMENT RITUALS - Martin, Jarred; van Wijk, Charles; Hans-Arendse, Chesray; Makhaba, Luvuyo (PINS-Psychology in Society, 2025)
The authors of this paper offer a turn to embodiment in exploring the role of bodies in “black”, South African bereavement rituals and mourning practices2 . This paper is born out of the trauma de-briefing program for the crew of a South African Navy vessel after the death of a comrade during an anti-piracy operation off the east coast of southern Africa. Herein we attempt to grapple with the unique complexities of the physical presence of bodies in African mourning rituals in the context of the deceased’s body being “lost at sea”. First we establish the operational context of naval deployment and the loss of the sailor’s body at sea. Second we outline some of the corporeal configurations of black South African bereavement rituals. Here we draw specific attention to bodies in processes of grief and mourning, for the deceased and mourners. Lastly, drawing on testimonies from four South African Navy personnel present during the operational deployment, we highlight the significant role played by bodies in African bereavement rituals. In sum, we suggest the need to re-matter the materiality of bodies in psychological literature on African bereavement rituals.